(untitled) (Research, Society and Development, 2020)
Introduction: Alzheimer’s disease (AD) is a progressive and irreversible neurodegenerative pathology that causes memory loss and several cognitive disorders, such as memory impairment, language difficulties and behavioral changes. This pathology appears with a higher prevalence in individuals with more advanced age (+65 years). Due to the characteristics of AD and its various complementary methods for diagnosis, the objective of this work was to evaluate the Proton Spectroscopy by Magnetic Resonance for diagnosis of this pathology. Methodology: This work refers to a qualitative exploratory literature search. In which searches were carried out on national and international databases, Medline, Scientific Electronic Electronic Library Online (SCIELO), Scholar Google (Google Scholar), Pubmed and Virtual Health Library (Bvs), considering studies in Portuguese languages ​​to be eligible. and English. Results: AD affects mainly people over 60 years of age, increasing the probability with the aging of individuals, since its manifestations occur due to cognitive and memory degradation, thus constituting a neurodegenerative pathology. The diagnosis of AD is pre-established with the exclusion of other possible causes for dementia. This exclusion is performed through clinical, laboratory and brain neuroimaging exams. Conclusion: The neuroimaging technique by proton spectroscopy in magnetic resonance demonstrates specificity in the quantification of the metabolites of N-acetylaspartate (NAA), Myo-inositol (MI), choline (Cho), Cho and Creatine (Cr) in AD, being a viable alternative for the in vivo study of the patient, since it does not represent an invasive analysis.